Preparation method of hydroxyapatite nanowire, polyether-ether-ketone / hydroxyapatite composite material and preparation method of polyether-ether-ketone / hydroxyapatite composite material
By preparing hydroxyapatite nanowires with high aspect ratio and combining them with polyether etherketone, the balance of mechanical properties and biological properties of composite materials in bone repair applications is solved, and better mechanical properties and biological activities are achieved, meeting the needs of clinical applications.
Patent Information
- Application Number
- CN202510019996.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
AI Technical Summary
Polyether etherketone/hydroxyapatite composites have problems with balance between mechanical properties and biological properties in bone repair applications, which makes it difficult to meet the needs in clinical applications.
By preparing hydroxyapatite nanowires with specific morphology and high aspect ratio and combining them with polyether ether ketone, hydroxyapatite nanowires were prepared by hydrothermal reaction method to improve their compatibility and mechanical properties with polyether ether ketone.
It improves the mechanical properties and biological activity of polyether etherketone/hydroxyapatite composites, meets the needs of bone repair applications, and provides better cell attachment and osteogenesis and differentiation capabilities.
Smart Images

Figure CN119822340A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of bone repair, and in particular to a method for preparing hydroxyapatite nanowires, a polyetheretherketone / hydroxyapatite composite material and a preparation method thereof. Background Art
[0002] Polyetheretherketone (PEEK) is a thermoplastic semi-crystalline polymer with good physical and chemical properties such as impact resistance, wear resistance, fatigue resistance, radiation resistance and corrosion resistance. In the biomedical field, polyetheretherketone is widely used in the repair and replacement of hard tissues due to its good chemical stability, mechanical properties and biocompatibility. However, polyetheretherketone is biologically inert and difficult to achieve effective bone integration, which limits its application in bone repair. In order to make up for this defect, researchers began to explore methods of compounding bioactive components with polyetheretherketone. Hydroxyapatite (HA) is the main inorganic component in human bones and has excellent biocompatibility, osteoconductivity and osteoinductivity. These properties make blending with hydroxyapatite an ideal method to make up for the lack of bioactivity of polyetheretherketone.
[0003] However, hydroxyapatite is internally bonded by ionic and covalent bonds, and it is difficult to carry out dislocation movement between lattices, which leads to its mechanical property defects of high brittleness and poor fatigue resistance. In addition, hydroxyapatite has poor interfacial compatibility with polyetheretherketone, and it is difficult to disperse evenly after being added to polyetheretherketone, and it is easy to agglomerate. These two reasons lead to the reduction of the mechanical properties of the polyetheretherketone matrix when blended with hydroxyapatite, making it difficult to meet actual clinical needs. How to achieve a balance between the mechanical properties and biological properties of polyetheretherketone / hydroxyapatite composites is a key problem in this field.
[0004] In the prior art, sulfonated polyetheretherketone is introduced into polyetheretherketone / hydroxyapatite composite materials to improve the interfacial compatibility of polyetheretherketone and hydroxyapatite to a certain extent. However, this method does not take into account the inherent brittleness of hydroxyapatite, and the addition of a large amount of fillers will still lead to a decrease in mechanical strength. Summary of the invention
[0005] The invention provides a method for preparing hydroxyapatite nanowires, a polyetheretherketone / hydroxyapatite composite material and a preparation method thereof. The hydroxyapatite nanowires prepared by the invention have good compatibility with polyetheretherketone and improve the mechanical properties of polyetheretherketone.
[0006] The present invention provides a method for preparing hydroxyapatite nanowires, comprising the following steps:
[0007] Mixing a monohydric alcohol, an aliphatic template, a basic compound, a calcium salt, a phosphate and water to obtain a suspension;
[0008] subjecting the suspension to a hydrothermal reaction to obtain the hydroxyapatite nanowires;
[0009] The temperature of the hydrothermal reaction is 160-240° C. and the time is 12-48 hours.
[0010] Preferably, the aliphatic templating agent comprises a long chain fatty acid.
[0011] Preferably, the long-chain fatty acid includes one or more of stearic acid, oleic acid, linoleic acid, lauric acid and palmitic acid.
[0012] Preferably, the mass ratio of the aliphatic template to the monohydroxy alcohol is 1:0.1-10;
[0013] The monohydric alcohol includes one or more of methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 1-pentanol and 1-hexanol.
[0014] Preferably, the alkaline compound includes one or more of sodium hydroxide, potassium hydroxide, ammonia water and ethylenediamine;
[0015] The concentration of the alkaline compound in the suspension is 0.2-2.0 mol / L.
[0016] Preferably, the calcium salt includes one or more of calcium chloride, calcium nitrate, calcium sulfate and calcium acetate;
[0017] The concentration of calcium salt in the suspension is 0.1-3.0 mol / L.
[0018] Preferably, the phosphate includes one or more of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium tripolyphosphate, sodium hexametaphosphate, potassium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium tripolyphosphate, potassium hexametaphosphate, ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium tripolyphosphate and ammonium hexametaphosphate;
[0019] The concentration of phosphate in the suspension is 0.1-3.0 mol / L.
[0020] The present invention also provides a polyetheretherketone / hydroxyapatite composite material, which comprises the following raw materials by mass fraction:
[0021]
[0022] The hydroxyapatite nanowires are hydroxyapatite nanowires prepared by the preparation method described in the above technical solution.
[0023] The present invention also provides a method for preparing the polyetheretherketone / hydroxyapatite composite material described in the above technical solution, characterized in that it comprises the following steps:
[0024] The raw materials of the polyetheretherketone / hydroxyapatite composite material are mixed, and then extrusion granulation and injection molding are performed in sequence to obtain the polyetheretherketone / hydroxyapatite composite material.
[0025] Preferably, after the injection molding, the method further comprises: sandblasting the molded product obtained by the injection molding.
[0026] The present invention prepares hydroxyapatite nanowires with specific morphology and high aspect ratio by selecting a suitable template (aliphatic template agent) and optimizing the temperature and time of the hydrothermal reaction. The hydroxyapatite nanowires with specific morphology and high aspect ratio maintain their inherent biological activity and exhibit excellent mechanical properties: when preparing polyetheretherketone / hydroxyapatite composite materials, the hydroxyapatite nanowires can play a reinforcing role in the composite material due to their high aspect ratio and bridging effect, thereby improving the overall mechanical properties of the composite material.
[0027] The preparation method of the polyetheretherketone / hydroxyapatite composite material of the present invention is simple and easy, the material performance is excellent, and it has a wide range of application prospects. By reasonably controlling the proportion of each component and the process parameters, a composite material with different biological activities and mechanical properties can be prepared to meet the needs of different bone repair applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a scanning electron microscope image of hydroxyapatite nanowires in Example 1;
[0029] Figure 2 is the X-ray diffraction pattern of hydroxyapatite nanowires of Example 1;
[0030] Figure 3 is a scanning electron microscopic image of the polyetheretherketone / hydroxyapatite composite material in Example 1;
[0031] Figure 4 is a tensile curve diagram of the polyetheretherketone / hydroxyapatite composite material in Example 1;
[0032] Figure 5 is a scanning electron microscope image of the tensile fracture surface of the polyetheretherketone / hydroxyapatite composite material in Example 1;
[0033] Figure 6 is the energy spectrum of the tensile section of the polyetheretherketone / hydroxyapatite composite material in Example 1;
[0034] Figure 7 is a total spectrum of the distribution diagram of the tensile section of the polyetheretherketone / hydroxyapatite composite material in Example 1;
[0035] Figure 8 is a bending performance diagram of the polyetheretherketone / hydroxyapatite composite material in Example 1;
[0036] Fig. 9 This is a graph showing the MC3T3-E1 cytotoxicity test of the polyetheretherketone / hydroxyapatite composite material in Example 1;
[0037] Fig.10 This is a bar graph showing the effect of the polyetheretherketone / hydroxyapatite composite material on the proliferation of MC3T3-E1 cells in Example 1;
[0038] Fig.11 This is a bar graph showing the effect of the polyetheretherketone / hydroxyapatite composite material in Example 1 on the osteogenic differentiation of MC3T3-E1 cells. DETAILED DESCRIPTION
[0039] The present invention provides a method for preparing hydroxyapatite nanowires, comprising the following steps:
[0040] Mixing a monohydric alcohol, an aliphatic template, a basic compound, a calcium salt, a phosphate and water to obtain a suspension;
[0041] subjecting the suspension to a hydrothermal reaction to obtain the hydroxyapatite nanowires;
[0042] The temperature of the hydrothermal reaction is 160-240° C. and the time is 12-48 hours.
[0043] The invention mixes monohydroxy alcohol, aliphatic template agent, alkaline compound, calcium salt, phosphate and water to obtain a suspension.
[0044] In the present invention, the mixing preferably includes:
[0045] The monohydric alcohol and the aliphatic template are first mixed to obtain a first mixture;
[0046] a second mixing of the alkaline compound and a portion of the water to obtain an alkaline solution;
[0047] The calcium salt is mixed with a portion of water for a third time to obtain a calcium salt solution;
[0048] mixing the phosphate with the remaining water for a fourth time to obtain a phosphate solution;
[0049] The first mixture, the alkaline solution, the calcium salt solution and the phosphate solution are subjected to a fifth mixing.
[0050] In the present invention, the mass ratio of the aliphatic template to the monohydric alcohol is preferably 1:0.1-10. In a specific embodiment of the present invention, the mass ratio of the aliphatic template to the monohydric alcohol can be 1:0.1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10; the aliphatic template preferably includes long-chain fatty acids; the long-chain fatty acids preferably include one or more of stearic acid, oleic acid, linoleic acid, lauric acid and palmitic acid; the monohydric alcohol includes one or more of methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 1-pentanol and 1-hexanol.
[0051] In the present invention, the concentration of the aliphatic template in the suspension is preferably 0.1-0.5 g / mL. In a specific embodiment of the present invention, the concentration of the aliphatic template in the suspension can be 0.1 g / mL, 0.2 g / mL, 0.3 g / mL, 0.4 g / mL or 0.5 g / mL.
[0052] In the present invention, the concentration of the alkaline compound in the suspension is preferably 0.2-2.0 mol / L. In a specific embodiment of the present invention, the concentration of the alkaline compound in the suspension can be 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L or 2.0 mol / L; the alkaline compound preferably includes one or more of sodium hydroxide, potassium hydroxide, ammonia water and ethylenediamine.
[0053] In the present invention, the concentration of calcium salt in the suspension is preferably 0.1-3.0 mol / L. In a specific embodiment of the present invention, the concentration of calcium salt in the suspension may be 0.1 mol / L, 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, 2.2 mol / L, 2.4 mol / L, 2.6 mol / L, 2.8 mol / L or 3 mol / L; the calcium salt preferably comprises one or more of calcium chloride, calcium nitrate, calcium sulfate and calcium acetate.
[0054] In the present invention, the concentration of phosphate in the suspension is preferably 0.1-3.0 mol / L. In a specific embodiment of the present invention, the concentration of phosphate in the suspension may be 0.1 mol / L, 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, 2.2 mol / L, 2.4 mol / L, 2.6 mol / L, 2.8 mol / L or 3 mol / L; the phosphate preferably comprises one or more of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium tripolyphosphate, sodium hexametaphosphate, potassium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium tripolyphosphate, potassium hexametaphosphate, ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium tripolyphosphate and ammonium hexametaphosphate.
[0055] After obtaining the suspension, the present invention performs a hydrothermal reaction on the suspension to obtain the hydroxyapatite nanowires.
[0056] In the present invention, the temperature of the hydrothermal reaction is 160-240°C, and the time is 12-48h. In a specific embodiment of the present invention, the temperature of the hydrothermal reaction can be 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C; the time can be 12h, 24h, 36h or 48h; the hydrothermal reaction is preferably carried out under closed conditions.
[0057] After the hydrothermal reaction, the present invention preferably further comprises: performing solid-liquid separation on the obtained product, and then washing the obtained solid with alcohol, water and drying.
[0058] The present invention has no particular limitation on the alcohol washing and water washing, and the unreacted raw materials and the alcohol used for the alcohol washing can be removed.
[0059] In the present invention, the hydroxyapatite nanowires preferably have a diameter of 10 to 100 nm and a length of 1 to 1000 μm.
[0060] The present invention also provides a polyetheretherketone / hydroxyapatite composite material, which comprises the following raw materials by mass fraction:
[0061]
[0062] The hydroxyapatite nanowires are hydroxyapatite nanowires prepared by the preparation method described in the above technical solution.
[0063] In the present invention, the raw materials of the polyetheretherketone / hydroxyapatite composite material include 1-40% hydroxyapatite nanowires by mass fraction. In a specific embodiment of the present invention, the mass fraction of the hydroxyapatite nanowires can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35% or 40%. Hydroxyapatite nanowires can improve the biological activity of the polyetheretherketone / hydroxyapatite composite material while maintaining the mechanical properties of the polyetheretherketone.
[0064] In the present invention, the raw materials of the polyetheretherketone / hydroxyapatite composite material include 0-3% of a coupling agent by mass fraction. In a specific embodiment of the present invention, the mass fraction of the coupling agent can be 0, 1%, 2% or 3%; the coupling agent preferably includes one or more of silane coupling agent KH550, silane coupling agent KH560, silane coupling agent KH570 and sulfonated polyetheretherketone.
[0065] In the present invention, the raw materials of the polyetheretherketone / hydroxyapatite composite material include 0-3% of plasticizer by mass fraction. In a specific embodiment of the present invention, the mass fraction of the plasticizer can be 0, 1%, 2% or 3%; the plasticizer preferably includes hyperbranched polyether substances and / or hyperbranched polysulfone substances; the hyperbranched polyether substances preferably include hyperbranched polyaryletherketone.
[0066] In the present invention, the raw materials of the polyetheretherketone / hydroxyapatite composite material include 0-3% of stabilizer by mass fraction. In a specific embodiment of the present invention, the mass fraction of the stabilizer can be 0, 1%, 2% or 3%; the stabilizer preferably includes titanium dioxide and / or silicon dioxide.
[0067] In the present invention, the raw material of the polyetheretherketone / hydroxyapatite composite material includes 0-3% lubricant by mass fraction. In a specific embodiment of the present invention, the mass fraction of the lubricant can be 0, 1%, 2% or 3%; the lubricant preferably includes polytetrafluoroethylene.
[0068] The introduction of additives (coupling agent, plasticizer, stabilizer, lubricant) can enhance the interfacial compatibility between polyetheretherketone and hydroxyapatite and further improve the overall performance of the composite material.
[0069] The present invention also provides a method for preparing the polyetheretherketone / hydroxyapatite composite material described in the above technical solution, comprising the following steps:
[0070] The raw materials of the polyetheretherketone / hydroxyapatite composite material are mixed, and then extrusion granulation and injection molding are performed in sequence to obtain the polyetheretherketone / hydroxyapatite composite material.
[0071] When the raw material includes a coupling agent, the preparation method preferably includes the following steps:
[0072] dispersing hydroxyapatite nanowires in N,N-dimethylformamide to obtain a dispersion;
[0073] dissolving a coupling agent in N,N-dimethylformamide to obtain a coupling agent solution;
[0074] The dispersion is mixed with a coupling agent solution to undergo a modification reaction and then separated, and the separated nanowires are washed and dried to obtain coupling agent-modified hydroxyapatite nanowires;
[0075] The coupling agent-modified hydroxyapatite nanowires are mixed with other raw materials of the polyetheretherketone / hydroxyapatite composite material, and then extrusion granulation and injection molding are performed in sequence.
[0076] In the present invention, the dispersion temperature is preferably 80° C., the dispersion time is preferably 1 h; and the concentration of the dispersion is preferably 0.1 to 0.5 g / mL.
[0077] In the present invention, the dissolution temperature is preferably 80° C.; the concentration of the coupling agent solution is preferably 0.01 to 0.1 g / mL.
[0078] In the present invention, the dispersion liquid and the coupling agent solution are preferably mixed in a protective atmosphere under stirring conditions.
[0079] In the present invention, the temperature of the extrusion granulation is preferably 360-400°C.
[0080] In the present invention, the injection temperature in the injection molding is preferably 360-400°C, and the mold temperature is preferably 200-240°C.
[0081] In the present invention, after the injection molding, the method preferably further comprises: subjecting the molded product obtained by the injection molding to sandblasting.
[0082] In the present invention, the sandblasting treatment preferably uses TiO2 particles for sandblasting, and the particle size of the TiO2 particles is preferably 180-220 μm. In a specific embodiment of the present invention, the particle size of the TiO2 particles can be 180 μm, 190 μm, 200 μm, 210 μm or 220 μm.
[0083] In the present invention, during the sandblasting treatment, the distance between the molded object and the nozzle is preferably 5 to 15 mm. In a specific embodiment of the present invention, the distance may be 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm or 15 mm;
[0084] In the present invention, during the sandblasting process, the angle at which the particle flow hits the surface of the molded object is preferably 60 to 90°. In a specific embodiment of the present invention, the angle may be 60°, 70°, 80° or 90°.
[0085] In the present invention, during the sandblasting, the airflow pressure is preferably 0.2-0.8 MPa. In a specific embodiment of the present invention, the airflow pressure may be 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa or 0.8 MPa;
[0086] In the present invention, the sandblasting time is preferably 10 to 30 seconds. In a specific embodiment of the present invention, the sandblasting time can be 10 seconds, 20 seconds or 30 seconds.
[0087] The present invention forms a rough structure on the surface of the composite material through sandblasting without reducing its mechanical strength, thereby increasing the surface roughness and exposing more hydroxyapatite sites, providing more space for bone cell growth and nutrient exchange, and improving biological performance.
[0088] After the sandblasting, the present invention preferably further comprises: washing and drying the molded product obtained by the sandblasting.
[0089] The preparation method of hydroxyapatite nanowires, the polyetheretherketone / hydroxyapatite composite material and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0090] The model of PTFE is Aladdin P434338;
[0091] Polyetheretherketone is from Jida Special Plastics, with a melt index of 34g / 10min (melted at 400℃ for 5min, and then the polymer flowing out within 10min was collected under a load of 5kg weight)
[0092] Example 1
[0093] At room temperature, 4.8 g of methanol and 9.8 g of oleic acid were mixed evenly, and 15 mL of 1.75 mol / L sodium hydroxide solution, 20 mL of 1.5 mol / L calcium chloride solution, and 20 mL of 3.0 mol / L sodium dihydrogen phosphate solution were gradually added dropwise, stirred evenly, and the mixed solution was transferred to a 100 mL hydrothermal reactor, sealed, and hydrothermally treated at 180 ° C for 24 h. After the reaction system was naturally cooled to room temperature, it was added to anhydrous ethanol and allowed to stand, and filtered after sedimentation. Subsequently, it was washed with anhydrous ethanol and deionized water for 5 times each, and the product was transferred to a blast oven and dried at 80 ° C for 12 h to obtain hydroxyapatite nanowires (diameter 60-80 nm, length 10-100 μm).
[0094] The hydroxyapatite nanowires, silane coupling agent KH560 and polyetheretherketone are weighed in proportions of 5%, 0.2% and 94.8% by mass, respectively.
[0095] The hydroxyapatite nanowires were dispersed in N,N-dimethylformamide by stirring, and the obtained dispersion was heated to 80°C and stirred for 1 hour. The concentration of hydroxyapatite in the dispersion was 0.5 g / mL;
[0096] Add the coupling agent to N,N-dimethylformamide, heat it to 80°C to completely dissolve it, and obtain a coupling agent solution with a coupling agent concentration of 0.1 g / mL;
[0097] The coupling agent solution was added to the dispersion kept at 80° C. for 1 hour, stirred at the constant temperature for 2 hours in a nitrogen atmosphere, and then filtered, washed with alcohol, washed with water and dried to obtain coupling agent-modified hydroxyapatite nanowires.
[0098] The hydroxyapatite nanowires modified by coupling agent were mixed with polyetheretherketone and extruded at 380℃ using a twin-screw extruder. After granulation, they were molded by injection molding. During this process, the injection temperature was 380℃ and the mold temperature was 220℃. The molded composite material was sandblasted with TiO2 particles. The TiO2 particle size was 220μm, the distance from the sample to the nozzle was 10mm, the angle of the particle flow hitting the sample surface was 90°, the air flow pressure was 0.5MPa, and the sandblasting time was 15s. After sandblasting, the parts were placed in an ultrasonic cleaner and washed three times with deionized water. After drying, polyetheretherketone / hydroxyapatite composite materials with synergistically enhanced bioactivity and mechanical properties were obtained.
[0099] Figure 1 This is a scanning electron microscope image of the hydroxyapatite nanowires in Example 1.
[0100] Depend on Figure 1 It can be seen that the prepared hydroxyapatite is linear and has good flexibility.
[0101] Figure 2 This is the X-ray diffraction pattern of the hydroxyapatite nanowires in Example 1.
[0102] Depend on Figure 2 It can be seen that the XRD spectrum of the product corresponds precisely to the diffraction peak position of the standard card (PDF#09-0432), the peak is sharp, and there is no diffraction peak of other phases, indicating that a single phase of hydroxyapatite is generated.
[0103] Figure 3 This is a scanning electron microscopic image of the polyetheretherketone / hydroxyapatite composite material in Example 1.
[0104] Depend on Figure 3 It can be seen that the surface morphology of the composite material is rough after sandblasting, which is conducive to better cell adhesion.
[0105] Figure 4 This is a tensile curve diagram of the polyetheretherketone / hydroxyapatite composite material in Example 1.
[0106] Depend on Figure 4 It can be seen that the addition of hydroxyapatite nanowires significantly improves the tensile strength of the material. After the addition of hydroxyapatite, the tensile strength of polyetheretherketone increases from 101.4MPa to 104.3MPa.
[0107] Figure 5 This is a scanning electron microscope image of the tensile fracture surface of the polyetheretherketone / hydroxyapatite composite material in Example 1.
[0108] Depend on Figure 5 It can be seen that hydroxyapatite nanowires are tightly combined with the polyetheretherketone matrix, and hydroxyapatite nanowires have a good reinforcement and toughening effect on polyetheretherketone.
[0109] Figure 6 is the energy spectrum of the tensile section of the polyetheretherketone / hydroxyapatite composite material in Example 1, Figure 7 This is the total number spectrum of the distribution diagram of the tensile section of the polyetheretherketone / hydroxyapatite composite material in Example 1.
[0110] Depend on Figures 6-7 It can be seen that the hydroxyapatite nanowires are uniformly distributed in the polyetheretherketone matrix.
[0111] Figure 8 This is a diagram showing the bending properties of the polyetheretherketone / hydroxyapatite composite material in Example 1.
[0112] Depend on Figure 8 It can be seen that the addition of hydroxyapatite nanowires significantly improves the flexural strength of the material. After adding hydroxyapatite, the flexural strength of polyetheretherketone increases from 155.2MPa to 172.1MPa.
[0113] Material Cell Cytotoxicity Testing: Live / Dead Cell Staining
[0114] The polyetheretherketone and polyetheretherketone / hydroxyapatite composite materials were sterilized by soaking in 75% alcohol for 30 minutes. After sterilization, the samples were washed three times with PBS buffer and once with complete medium. The materials were placed in a 12-well plate, and 1 mL of complete medium was added to each well; MC3T3-E1 cell suspension was added to each well to inoculate cells, and the inoculation density was 2×10 4 Each well was incubated in a carbon dioxide incubator at 37°C for 24 hours. After 24 hours of incubation, the culture medium was discarded, the material was taken out, 200 μL of Calcein-AM / PI staining working solution was added to each well, and incubated for 20 minutes. After staining, PBS was washed three times and observed under a fluorescent inverted microscope. The part that produced green fluorescence under the microscope was living cells, and the part that produced red fluorescence was dead cells.
[0115] Effects of materials on cell proliferation: CCK-8 assay
[0116] The cells were co-cultured with the materials for 1, 4, and 7 days, respectively, with the same cell inoculation steps. 100 μL CCK-8 reagent was added to each well and incubated for 2 h. The liquid was transferred to a 96-well plate and the absorbance at a wavelength of 420 nm was measured using an ELISA analyzer.
[0117] Cell viability = [(experimental well - blank well) / (negative control well - blank well)] × 100%
[0118] Effects of materials on osteogenic differentiation of cells: ALP detection method
[0119] The cells and materials were co-cultured for 7 days and 14 days respectively, in the same cell inoculation step as above. 500 μL of trypsin-EDTA digestion solution was added to each well for 3 min of digestion. After adding 500 μL of complete medium to terminate the digestion, the cell pellet was obtained by centrifugation, and then the cell lysis solution was added to lyse the cells to obtain the sample to be tested. According to the measurement of the ALP detection kit manual, the sample to be tested and each working solution were added to a 96-well plate, and the absorbance value at a wavelength of 520 nm was measured with an enzyme-labeled analyzer.
[0120] ALP activity = [(A 测定 -A 空白 ) / (A 标准 -A 空白 )]*C 标准 / C pr
[0121] C 标准 : Phenol standard solution concentration, 0.1 mg / mL; C pr : Sample protein concentration; A: absorbance value of each well.
[0122] Fig. 9 This is a graph showing the MC3T3-E1 cytotoxicity test of the polyetheretherketone / hydroxyapatite composite material in Example 1.
[0123] Depend on Fig. 9 It can be seen that there were no red-stained dead cells in the polyetheretherketone and polyetheretherketone / hydroxyapatite composite material groups co-cultured with MC3T3-E1 cells for 24 hours, proving that the materials had no cytotoxicity.
[0124] Fig.10 This is a bar graph showing the effect of the polyetheretherketone / hydroxyapatite composite material in Example 1 on the proliferation of MC3T3-E1 cells.
[0125] Depend on Fig.10 It can be seen that the cell viability of the polyetheretherketone / hydroxyapatite composite material group was higher than that of the pure polyetheretherketone group when co-cultured with MC3T3-E1 cells for 1, 4, and 7 days, which proves that the polyetheretherketone / hydroxyapatite composite material has good cell activity, can provide a suitable microenvironment for cells, and effectively promote cell proliferation.
[0126] Fig.11 This is a bar graph showing the effect of the polyetheretherketone / hydroxyapatite composite material in Example 1 on the osteogenic differentiation of MC3T3-E1 cells.
[0127] Depend on Fig.11 It can be seen that the ALP activity of the polyetheretherketone / hydroxyapatite composite material group was higher than that of the pure polyetheretherketone group when co-cultured with MC3T3-E1 cells for 7 and 14 days, which proves that the incorporation of hydroxyapatite nanowires significantly improves the ability of the material to promote cell osteogenic differentiation.
[0128] Example 2
[0129] At room temperature, 4.7 g of ethanol and 9.8 g of oleic acid were mixed evenly, and 15 mL of 1.75 mol / L sodium hydroxide solution, 20 mL of 1.5 mol / L calcium chloride solution, and 20 mL of 3.0 mol / L sodium dihydrogen phosphate solution were gradually added dropwise, stirred evenly, and the mixed solution was transferred to a 100 mL hydrothermal reactor, sealed, and hydrothermally treated at 180 ° C for 24 h. After the reaction system was naturally cooled to room temperature, it was added to anhydrous ethanol and allowed to stand, and filtered after sedimentation. Subsequently, it was washed with anhydrous ethanol and deionized water for 5 times each, and the product was transferred to a blast oven and dried at 80 ° C for 12 h to obtain hydroxyapatite nanowires (diameter 60-80 nm, length 10-100 μm).
[0130] The above-mentioned hydroxyapatite nanowires, silane coupling agent KH560, polytetrafluoroethylene and polyetheretherketone are weighed in proportions of 10%, 0.2%, 0.2% and 89.6% by mass, respectively.
[0131] The hydroxyapatite nanowires were dispersed in N,N-dimethylformamide by stirring, and the obtained dispersion was heated to 80°C and stirred for 1 hour. The concentration of hydroxyapatite in the dispersion was 0.5 g / mL;
[0132] Add the coupling agent to N,N-dimethylformamide, heat it to 80°C to completely dissolve it, and obtain a coupling agent solution with a coupling agent concentration of 0.1 g / mL;
[0133] The coupling agent solution was added to the dispersion kept at 80° C. for 1 hour, stirred at the constant temperature for 2 hours in a nitrogen atmosphere, and then filtered, washed with alcohol, washed with water and dried to obtain coupling agent-modified hydroxyapatite nanowires.
[0134] The hydroxyapatite nanowires modified by coupling agent, polytetrafluoroethylene and polyetheretherketone were mixed and extruded at 380℃ using a twin-screw extruder. After granulation, they were molded by injection molding. During this process, the injection temperature was 380℃ and the mold temperature was 220℃. The molded composite material was sandblasted with TiO2 particles. The TiO2 particle size was 220μm, the distance from the sample to the nozzle was 10mm, the angle of the particle flow hitting the sample surface was 90°, the air flow pressure was 0.5MPa, and the sandblasting time was 15s. After sandblasting, the parts were placed in an ultrasonic cleaner and washed three times with deionized water. After drying, polyetheretherketone / hydroxyapatite composite materials with synergistically enhanced bioactivity and mechanical properties were obtained.
[0135] Example 3
[0136] At room temperature, 4.7 g of methanol and 9.8 g of oleic acid were mixed evenly, and 15 mL of 1.75 mol / L sodium hydroxide solution, 20 mL of 1.5 mol / L calcium chloride solution, and 20 mL of 2.5 mol / L sodium dihydrogen phosphate solution were gradually added dropwise, stirred evenly, and the mixed solution was transferred to a 100 mL hydrothermal reactor, sealed, and hydrothermally treated at 180 ° C for 24 h. After the reaction system was naturally cooled to room temperature, it was added to anhydrous ethanol and allowed to stand, and filtered after sedimentation. Subsequently, it was washed with anhydrous ethanol and deionized water for 5 times each, and the product was transferred to a blast oven and dried at 80 ° C for 12 h to obtain hydroxyapatite nanowires (diameter 50-80 nm, length 10-50 μm).
[0137] The above-mentioned hydroxyapatite nanowires, KH560, polytetrafluoroethylene, hyperbranched polyaryletherketone and polyetheretherketone are weighed in proportions of 15%, 0.2%, 0.2%, 0.2% and 89.4% by mass, respectively.
[0138] The hydroxyapatite nanowires were dispersed in N,N-dimethylformamide by stirring, and the obtained dispersion was heated to 80°C and stirred for 1 hour. The concentration of hydroxyapatite in the dispersion was 0.5 g / mL;
[0139] Add the coupling agent to N,N-dimethylformamide, heat it to 80°C to completely dissolve it, and obtain a coupling agent solution with a coupling agent concentration of 0.1 g / mL;
[0140] The coupling agent solution was added to the dispersion kept at 80° C. for 1 hour, stirred at the constant temperature for 2 hours in a nitrogen atmosphere, and then filtered, washed with alcohol, washed with water and dried to obtain coupling agent-modified hydroxyapatite nanowires.
[0141] The hydroxyapatite nanowires modified by coupling agent, polytetrafluoroethylene, hyperbranched polyaryletherketone and polyetheretherketone are mixed and extruded at 390℃ using a twin-screw extruder. After granulation, they are molded by injection molding. During this process, the injection temperature is 390℃ and the mold temperature is 220℃. The molded composite material is sandblasted with TiO2 particles. The TiO2 particle size is 220μm, the distance from the sample to the nozzle is 10mm, the angle of the particle flow hitting the sample surface is 90°, the air flow pressure is 0.5MPa, and the sandblasting time is 15s. After sandblasting, the parts are placed in an ultrasonic cleaner and washed three times with deionized water. After drying, polyetheretherketone / hydroxyapatite composite materials with synergistically enhanced bioactivity and mechanical properties are obtained.
[0142] Example 4
[0143] At room temperature, 4.7 g of ethanol and 9.8 g of oleic acid were mixed evenly, and 15 mL of 1.75 mol / L sodium hydroxide solution, 20 mL of 1.5 mol / L calcium chloride solution, and 20 mL of 3.0 mol / L sodium dihydrogen phosphate solution were gradually added dropwise, stirred evenly, and the mixed solution was transferred to a 100 mL hydrothermal reactor, sealed, and hydrothermally treated at 180 ° C for 12 h. After the reaction system was naturally cooled to room temperature, it was added to anhydrous ethanol and allowed to stand, and filtered after sedimentation. Subsequently, it was washed with anhydrous ethanol and deionized water for 5 times each, and the product was transferred to a blast oven and dried at 80 ° C for 12 h to obtain hydroxyapatite nanowires (diameter 20-80 nm, length 10-100 μm).
[0144] The above-mentioned hydroxyapatite nanowires, sulfonated polyetheretherketone and polyetheretherketone are weighed in proportions of 20%, 0.2% and 79.8% by mass, respectively.
[0145] The hydroxyapatite nanowires were dispersed in N,N-dimethylformamide by stirring, and the obtained dispersion was heated to 80°C and stirred for 1 hour. The concentration of hydroxyapatite in the dispersion was 0.5 g / mL;
[0146] Add the coupling agent to N,N-dimethylformamide, heat it to 80°C to completely dissolve it, and obtain a coupling agent solution with a coupling agent concentration of 0.1 g / mL;
[0147] The coupling agent solution was added to the dispersion kept at 80° C. for 1 hour, stirred at the constant temperature for 2 hours in a nitrogen atmosphere, and then filtered, washed with alcohol, washed with water and dried to obtain coupling agent-modified hydroxyapatite nanowires.
[0148] The coupling agent-modified hydroxyapatite nanowires and polyetheretherketone were mixed and extruded at 390°C using a twin-screw extruder. After granulation, the composite material was molded by injection molding. During this process, the injection temperature was 390°C and the mold temperature was 220°C. The molded composite material was sandblasted with TiO2 particles. The TiO2 particle size was 220μm, the distance from the sample to the nozzle was 10mm, the angle of the particle flow hitting the sample surface was 90°, the air flow pressure was 0.5MPa, and the sandblasting time was 15s. After sandblasting, the product was placed in an ultrasonic cleaner and washed three times with deionized water. After drying, a polyetheretherketone / hydroxyapatite composite material with synergistically enhanced bioactivity and mechanical properties was obtained.
[0149] Example 5
[0150] At room temperature, 4.7 g of methanol and 9.9 g of linoleic acid were mixed evenly, and 15 mL of 1.75 mol / L sodium hydroxide solution, 20 mL of 1.5 mol / L calcium chloride solution, and 20 mL of 2.25 mol / L sodium dihydrogen phosphate solution were gradually added dropwise, stirred evenly, and the mixed solution was transferred to a 100 mL hydrothermal reactor, sealed, and hydrothermally treated at 180 ° C for 12 h. After the reaction system was naturally cooled to room temperature, it was added to anhydrous ethanol and allowed to stand, and filtered after sedimentation. Subsequently, it was washed with anhydrous ethanol and deionized water for 5 times each, and the product was transferred to a blast oven and dried at 80 ° C for 12 h to obtain hydroxyapatite nanowires (diameter 20-80 nm, length 10-50 μm).
[0151] The above-mentioned hydroxyapatite nanowires, sulfonated polyetheretherketone and polyetheretherketone are weighed in proportions of 10%, 0.2% and 89.8% by mass, respectively.
[0152] The hydroxyapatite nanowires were dispersed in N,N-dimethylformamide by stirring, and the obtained dispersion was heated to 80°C and stirred for 1 hour. The concentration of hydroxyapatite in the dispersion was 0.5 g / mL;
[0153] Add the coupling agent to N,N-dimethylformamide, heat it to 80°C to completely dissolve it, and obtain a coupling agent solution with a coupling agent concentration of 0.1 g / mL;
[0154] The coupling agent solution was added to the dispersion kept at 80° C. for 1 hour, stirred at the constant temperature for 2 hours in a nitrogen atmosphere, and then filtered, washed with alcohol, washed with water and dried to obtain coupling agent-modified hydroxyapatite nanowires.
[0155] The hydroxyapatite nanowires modified by coupling agent and polyetheretherketone were mixed and extruded at 380℃ using a twin-screw extruder. After granulation, they were molded by injection molding. During this process, the injection temperature was 380℃ and the mold temperature was 220℃. The molded composite material was sandblasted with TiO2 particles. The TiO2 particle size was 220μm, the distance from the sample to the nozzle was 10mm, the angle of the particle flow hitting the sample surface was 90°, the air flow pressure was 0.5MPa, and the sandblasting time was 15s. After sandblasting, the parts were placed in an ultrasonic cleaner and washed three times with deionized water. After drying, polyetheretherketone / hydroxyapatite composite materials with synergistically enhanced bioactivity and mechanical properties were obtained.
[0156] Example 6
[0157] At room temperature, 8 g of lauric acid and 12 g of methanol were mixed evenly, and 15 mL of 1.75 mol / L sodium hydroxide solution, 20 mL of 1.5 mol / L calcium chloride solution, and 20 mL of 3.0 mol / L sodium dihydrogen phosphate solution were gradually added dropwise and stirred evenly. The mixed solution was transferred to a 100 mL hydrothermal reactor, sealed, and hydrothermally treated at 180 ° C for 12 h. After the reaction system was naturally cooled to room temperature, it was added to anhydrous ethanol and allowed to stand. After it was precipitated, it was filtered, and then washed with anhydrous ethanol and deionized water for 5 times respectively. The product was transferred to a blast oven and dried at 80 ° C for 12 h to obtain hydroxyapatite nanowires (diameter 20-40 nm, length 10-100 μm).
[0158] The above-mentioned hydroxyapatite nanowires, sulfonated polyetheretherketone and polyetheretherketone are weighed into raw materials in a ratio of 10%, 0.5% and 89.5% by mass respectively.
[0159] The hydroxyapatite nanowires were dispersed in N,N-dimethylformamide by stirring, and the obtained dispersion was heated to 80°C and stirred for 1 hour. The concentration of hydroxyapatite in the dispersion was 0.5 g / mL;
[0160] Add the coupling agent to N,N-dimethylformamide, heat it to 80°C to completely dissolve it, and obtain a coupling agent solution with a coupling agent concentration of 0.1 g / mL;
[0161] The coupling agent solution was added to the dispersion kept at 80° C. for 1 hour, stirred at the constant temperature for 2 hours in a nitrogen atmosphere, and then filtered, washed with alcohol, washed with water and dried to obtain coupling agent-modified hydroxyapatite nanowires.
[0162] The hydroxyapatite nanowires modified by coupling agent and polyetheretherketone were mixed and extruded at 380℃ using a twin-screw extruder. After granulation, they were molded by injection molding. During this process, the injection temperature was 380℃ and the mold temperature was 220℃. The molded composite material was sandblasted with TiO2 particles. The TiO2 particle size was 220μm, the distance from the sample to the nozzle was 10mm, the angle of the particle flow hitting the sample surface was 90°, the air flow pressure was 0.5MPa, and the sandblasting time was 15s. After sandblasting, the parts were placed in an ultrasonic cleaner and washed three times with deionized water. After drying, polyetheretherketone / hydroxyapatite composite materials with synergistically enhanced bioactivity and mechanical properties were obtained.
[0163] Example 7
[0164] At room temperature, 8 g of stearic acid and 12 g of methanol were mixed evenly, and 15 mL of 1.75 mol / L sodium hydroxide solution, 20 mL of 1.5 mol / L calcium chloride solution, and 20 mL of 2.25 mol / L sodium dihydrogen phosphate solution were gradually added dropwise, stirred evenly, and the mixed solution was transferred to a 100 mL hydrothermal reactor, sealed, and hydrothermally treated at 180 ° C for 12 h. After the reaction system was naturally cooled to room temperature, it was added to anhydrous ethanol and allowed to stand, and filtered after sedimentation. Subsequently, it was washed with anhydrous ethanol and deionized water for 5 times each, and the product was transferred to a blast oven and dried at 80 ° C for 12 h to obtain hydroxyapatite nanowires (diameter 60-80 nm, length 5-20 μm).
[0165] The above-mentioned hydroxyapatite nanowires and polyetheretherketone are mixed in a ratio of 10% and 90% by mass, and extruded at 380°C using a twin-screw extruder. After granulation, they are molded by injection molding. During this process, the injection temperature is 380°C and the mold temperature is 220°C. The molded composite material is sandblasted with TiO2 particles. The TiO2 particle size is 220μm, the distance from the sample to the nozzle is 10mm, the angle of the particle flow hitting the sample surface is 90°, the air flow pressure is 0.5MPa, and the sandblasting time is 15s. After sandblasting, the parts are placed in an ultrasonic cleaner and washed three times with deionized water. After drying, polyetheretherketone / hydroxyapatite composite materials with synergistically enhanced bioactivity and mechanical properties are obtained.
[0166] According to GB / T1040.1-2018 and GB / T9341-2008, the tensile and bending strength of the polyetheretherketone / hydroxyapatite composite materials of Examples 1 to 7 and the polyetheretherketone samples used in Examples 1 to 7 were tested respectively. The tensile spline had a gauge length of 25 mm, a width of 5 mm, and a thickness of 2 mm, and the bending spline had a length of 80 mm, a width of 10 mm, and a thickness of 4 mm.
[0167] Tensile Strength and Flexural Strength of Polyetheretherketone / Hydroxyapatite Composite Materials of Examples 1 to 7 and Polyetheretherketone Used in Examples 1 to 7
[0168] sample Tensile strength(MPa) Bending strength(MPa) Polyetheretherketone 101.4 155.2 Example 1 104.3 172.1 Example 2 109.6 179.7 Example 3 116.6 189.4 Example 4 101.9 184.6 Example 5 104.1 183.4 Example 6 108.9 181.1 Example 7 101.9 165.7
[0169] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing hydroxyapatite nanowires, characterized in that: The following steps are involved: Mixing a monohydric alcohol, an aliphatic template, a basic compound, a calcium salt, a phosphate and water to obtain a suspension; subjecting the suspension to a hydrothermal reaction to obtain the hydroxyapatite nanowires; The temperature of the hydrothermal reaction is 160-240° C. and the time is 12-48 hours.
2. The preparation method according to claim 1, characterized in that: The aliphatic templating agent includes long chain fatty acids.
3. The preparation method according to claim 2, characterized in that: The long-chain fatty acids include one or more of stearic acid, oleic acid, linoleic acid, lauric acid and palmitic acid.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The mass ratio of the aliphatic template agent to the monohydroxy alcohol is 1:0.1-10; The monohydric alcohol includes one or more of methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 1-pentanol and 1-hexanol.
5. The preparation method according to claim 1, characterized in that: The alkaline compound includes one or more of sodium hydroxide, potassium hydroxide, ammonia water and ethylenediamine; The concentration of the alkaline compound in the suspension is 0.2-2.0 mol / L.
6. The preparation method according to claim 1, characterized in that: The calcium salt includes one or more of calcium chloride, calcium nitrate, calcium sulfate and calcium acetate; The concentration of calcium salt in the suspension is 0.1-3.0 mol / L.
7. The preparation method according to claim 1, characterized in that: The phosphate includes one or more of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium tripolyphosphate, sodium hexametaphosphate, potassium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium tripolyphosphate, potassium hexametaphosphate, ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium tripolyphosphate and ammonium hexametaphosphate; The concentration of phosphate in the suspension is 0.1-3.0 mol / L.
8. A polyetheretherketone / hydroxyapatite composite material, characterized in that: In terms of mass fraction, it includes the following raw materials: The balance is polyetheretherketone; The hydroxyapatite nanowires are hydroxyapatite nanowires prepared by the preparation method according to any one of claims 1 to 7.
9. The method for preparing the polyetheretherketone / hydroxyapatite composite material according to claim 8, characterized in that: The following steps are involved: The raw materials of the polyetheretherketone / hydroxyapatite composite material are mixed, and then extrusion granulation and injection molding are performed in sequence to obtain the polyetheretherketone / hydroxyapatite composite material.
10. The preparation method according to claim 9, characterized in that: After the injection molding, the method further includes: sandblasting the molded product obtained by the injection molding.
Citation Information
Patent Citations
Nano-hydroxyapatite / polyether-ether-ketone composite material and bone repair body as well as preparation method and application thereof
CN104974467A
Poly(ether-ether-ketone) surface modification method and poly(ether-ether-ketone) obtained through modification and application thereof
CN113527748A
Preparation method of hydroxyapatite composite hydroxyl manganese oxide nano reticular catalyst
CN116571259A
Inorganically surface-modified polymers and methods for making and using them
US20120010599A1
Components incorporating bioactive material
US20140035201A1
Cited By
Water purifying agent for aquaculture and preparation method thereof
CN120058084A